(untitled) (Research, Society and Development, 2021)
Serpentinite application can reduce soil acidity by increasing Ca, Mg, P, and Si to plants. The objective of this work was to evaluate the influence of serpentinite on the production of shoot dry matter of the forage Urochloa brizantha cv. Piatã and forage phytomass decomposition. The experimental design used was randomized blocks in sub-divided plots in time, with the doses of serpentinite in the plots (0, 2, 4, 8, and 16 mg ha-1), the use of bioactive in the subplots (with and without the use of bioactive) and the evaluation times in the sub-sub plots (0, 30, 60, 90, 120 and 150 days after management). The variables analyzed were: phytomass coverage rate on the ground, remaining mass, half-life, and constant forage phytomass decomposition. The application of serpentinite provided higher matter productivity, increased the coverage rate and the remaining mass of Urochloa brizantha phytomass on the soil. The use of the bioactive provided more excellent forage dry matter production with lower doses of serpentinite.